Greater Body Fatness Is Associated With Higher Protein Expression of LEPR in Breast Tumor Tissues: A Cross-Sectional Analysis in the Women’s Circle of Health Study - Llanos, Adana A.M.; Aremu, John B.; Cheng, Ting-Yuan David; Chen, Wenjin; Chekmareva, Marina A.; Cespedes Feliciano, Elizabeth M.; Qin, Bo; Lin, Yong; Omene, Coral; Khoury, Thaer; Hong, Chi-Chen; Yao, Song; et al. (Frontiers in Endocrinology, 2022)
Background: The mechanisms underlying the association of overall and central body fatness with poorer breast cancer outcomes remain unclear; altered gene and/or protein expression of the adipokines and their receptors might play a role. Methods: In a sample of Black and White women with primary invasive breast cancer, we investigated associations of body mass index (BMI), waist circumference, hip circumference, waist-to-hip ratio (WHR), fat mass index (FMI), and percent body fat with protein expression (log-transformed, n = 722) and gene expression (log2-transformed, n = 148) of leptin (LEP), leptin receptor (LEPR), adiponectin (ADIPOQ), and adiponectin receptors 1 and 2 (ADIPOR1, ADIPOR2). Multivariable linear models, adjusting for race, menopausal status, and estrogen receptor status, were used to assess these associations, with Bonferroni correction for multiple comparisons. Results: In multivariable models, we found that increasing BMI (beta = 0.0529, 95% CI: 0.0151, 0.0906) and FMI (beta= 0.0832, 95% CI: 0.0268, 0.1397) were associated with higher LEP gene expression, corresponding to 34.5% and 38.3% increases in LEP gene expression for a standard deviation (SD) increase in BMI and FMI, respectively. Increasing BMI (beta = 0.0028, 95% CI: 0.0011, 0.0045), waist circumference (beta = 0.0013, 95% CI: 0.0005, 0.0022), hip circumference (beta = 0.0015, 95% CI: 0.0007, 0.0024), and FMI (beta = 0.0041, 95% CI: 0.0015, 0.0067) were associated with higher LEPR protein expression. These associations equate to 16.8%, 17.6%, 17.7%, 17.2% increases in LEPR protein expression for a 1-SD increase in BMI, waist circumference, hip circumference, and FMI, respectively. Further, these associations were stronger among White and postmenopausal women and ER+ cases; formal tests of interaction yielded evidence of effect modification by race. No associations of body fatness with LEP protein expression, LEPR gene expression, or protein or gene expression of ADIPOQ, ADIPOR1, and ADIPOR2 were found. Conclusions: These findings support an association of increased body fatness – beyond overall body size measured using BMI – with higher LEP gene expression and higher LEPR protein expression in breast tumor tissues. Clarifying the impact of adiposity-related adipokine and adipokine receptor expression in breast tumors on long-term breast cancer outcomes is a critical next step.